2022
DOI: 10.3390/molecules27092941
|View full text |Cite
|
Sign up to set email alerts
|

The Lactoferrin Phenomenon—A Miracle Molecule

Abstract: Numerous harmful factors that affect the human body from birth to old age cause many disturbances, e.g., in the structure of the genome, inducing cell apoptosis and their degeneration, which leads to the development of many diseases, including cancer. Among the factors leading to pathological processes, microbes, viruses, gene dysregulation and immune system disorders have been described. The function of a protective agent may be played by lactoferrin as a “miracle molecule”, an endogenous protein with a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 150 publications
0
46
0
Order By: Relevance
“…Lactoferrin (LF, lactotransferrin) is a nonheme multifunctional cationic natural protein found in exocrine secretions and in the secondary granules of neutrophils [ 26 , 27 , 28 , 29 ]. The characteristic functions of this protein includes binding of toxic free-iron.…”
Section: Introductionmentioning
confidence: 99%
“…Lactoferrin (LF, lactotransferrin) is a nonheme multifunctional cationic natural protein found in exocrine secretions and in the secondary granules of neutrophils [ 26 , 27 , 28 , 29 ]. The characteristic functions of this protein includes binding of toxic free-iron.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have shown mixed reports that bovine LF-fortified formula given to neonates and infants reduces the incidence of diarrhoeal illness and respiratory disease (King et al 2007 ; Chen et al 2016 ). To explain these findings, it is proposed that orally delivered bovine LF (bLF) alters the gut microbiota and gut mucosal immune system, modulating the immunity of other mucous membranes such as the respiratory tract (Chen et al 2016 ; Kowalczyk et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two models have been proposed. The first is that LF and its degradation products could exert distal effects even if it remains in the wall of the gut (Kowalczyk et al 2022 ). This could occur by interaction of LF with gut associated lymphoid tissue (Kilic et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…. cells at all stages of life (Spadaro et al, 2008;Kowalczyk et al, 2022). LF is endowed with extensive biological properties, including antibacterial, antiviral, anti-inflammatory, antioxidant, anticarcinogenic, immunomodulatory, and enzymatic activities (García-Montoya et al, 2012;da et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…LF is widely present in many mammalian secretions, including mammalian milk, saliva, tears, bronchial and intestinal secretions, and secondary granules of neutrophils (Katunuma et al, 2003 ). Known as a natural antibiotic, it is an important component that bridges the innate and adaptive immune systems of mammals and plays roles in protecting human cells at all stages of life (Spadaro et al, 2008 ; Kowalczyk et al, 2022 ). LF is endowed with extensive biological properties, including antibacterial, antiviral, anti-inflammatory, antioxidant, anticarcinogenic, immunomodulatory, and enzymatic activities (García-Montoya et al, 2012 ; da et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%